2022
DOI: 10.3390/cancers14153591
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Oncogenic and Immune-Response Pathways Is Linked to Disease-Specific Survival in Merkel Cell Carcinoma

Abstract: Background: Merkel cell carcinoma (MCC) is a rare but highly aggressive neuroendocrine carcinoma of the skin with a poor prognosis. Improving the prognosis of MCC by means of targeted therapies requires further understanding of the mechanisms that drive tumor progression. In this study, we aimed to identify the genes, processes, and pathways that play the most crucial roles in determining MCC outcomes. Methods: We investigated transcriptomes generated by RNA sequencing of formalin-fixed paraffin-embedded tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…However, 3′ tag counting, which was used during RNA sequencing in our study, significantly improves specificity when examining differential gene expression of samples with low RIN 29 . Previously, we found a strong correlation between the logFC values of genes based on MCPyV status when comparing the transcriptomic data used in our study with transcriptomic data obtained from fresh frozen tissues provided by Harms et al (GSE39612), suggesting a high specificity of our transcriptomic data when studying differentially expressed genes, as compared with data from fresh frozen tissues 16,30 . Our findings could be further validated by studying an independent MCC cohort as well as validating RNA sequencing data using a different methodology, for example, quantitative PCR.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…However, 3′ tag counting, which was used during RNA sequencing in our study, significantly improves specificity when examining differential gene expression of samples with low RIN 29 . Previously, we found a strong correlation between the logFC values of genes based on MCPyV status when comparing the transcriptomic data used in our study with transcriptomic data obtained from fresh frozen tissues provided by Harms et al (GSE39612), suggesting a high specificity of our transcriptomic data when studying differentially expressed genes, as compared with data from fresh frozen tissues 16,30 . Our findings could be further validated by studying an independent MCC cohort as well as validating RNA sequencing data using a different methodology, for example, quantitative PCR.…”
Section: Discussionsupporting
confidence: 64%
“…Harms et al (GSE39612), suggesting a high specificity of our transcriptomic data when studying differentially expressed genes, as compared with data from fresh frozen tissues. 16,30 Our findings could be further validated by studying an independent MCC cohort as well as validating RNA sequencing data using a different methodology, for example, quantitative PCR.…”
Section: Years After Diagnosismentioning
confidence: 60%
See 2 more Smart Citations
“…While there are limited whole transcriptomic studies utilizing MCC patient tumors at the single-cell and bulk RNA-seq levels, we identified a recent study with the largest published cohort of MCC patient tumors to date. 42 In the study, bulk RNA-seq was performed on 102 archival MCC tumors, and gene expression was correlated with clinical data, resulting in the identification of key marker genes associated with patient survival and death. These signatures, referred to as survival-associated genes (SAGs) and death-associated genes (DAGs), pointed toward an enrichment of oncogenic and immune-response pathways in conferring survival to MCC patients.…”
Section: Resultsmentioning
confidence: 99%